Development and implementation of new methods to analyse technical-tactical actions in the sport of judo - Oswald, R.; Heinisch, H. D.; Heinrich, J.; Büsch, D. (7th IJF SYMPOSIUM, Paris 22 August 2011, 2011)
analyse technical tactical actions during competition-like training was made. During the direct competition preparation for the ECh and the WCh, training matches of elite athletes were analysed and recommendations for training were given. As a new issue, individual goals for performance (individual fighting concept-IKZ) and the control of their implementation were integrated. So it was shown that the method is useful to determine the individual technical tactical performance capacity. The direct reference to the video material and the opportunity to make error analyses allow for faster and more effective corrections and determinations of priorities during the training. After corrections as a result of the first testing phase the new analysis methods were applied in 2010 in the competition analysis of selected athletes at the ECh (see table 2). Another upgrade of the systems is planned until 2012.